Impact of The Enforcement of ASEAN Economic Community on Policy and Strategy of Sea Transportation Development in Indonesia - Aflah, Aflah; Purba, Hasim; Suhaidi, Suhaidi; Siregar, Mahmul (Indonesian Journal of International Law, 2023)
This study aimed to determine the impact of the ASEAN Economic Community (AEC) on the national shipping industry highly imbalanced with relevant business policies. The AEC agreement is also expected to positively affect the shipping industry while controlling domestic and competing in international activities. In this study, a normative method was used, with the collection of data carried out through literature studies. The Maritime Vision of Indonesia, which is the Policy Direction and Strategy for The Development of Marine Transportation, was also implemented to motivate the country toward becoming the World Maritime Axis. This emphasized becoming a developed, sovereign, independent, and strong maritime country, which was able to positively contribute to regional and global security and peace, according to national interests. Furthermore, the Marine Policy of Indonesia was prepared regarding the Development Vision of the country, as stated in Law Number 17 of 2007 concerning the National Long-Term Development Plan 2005-2025 and Law Number 32 of 2014 emphasizing Marine Affairs. The results showed that the implementation of ASSM (ASEAN Shipping Single Market) impacted the national shipping industry, due to increasingly open competition. Based on the AEC era, Indonesia should be internally and externally ready, for the effective and efficient prioritization of shipping transportation activities. The country should also be ready to compete nationally and internationally, specifically in sea transportation, as one of the important components of the national shipping sector.